Is semen analysis necessary prior to the commencement of testosterone supplementation therapy in men of reproductive age? - Pan, Michael; Ramasamy, Ranjith; Kovac, Jason Ronald (Canadian Urological Association Journal, 2014)
A semen analysis (SA) should be performed on all men of reproductive age prior to the commencement of testosterone supplementation therapy (TST).  A baseline SA has numerous benefits including the ability to unmask occult azoospermia, act as a baseline measure of reproductive function, and provide a recovery target for management of TST-induced testicular dysfunction.  Physicians treating men of reproductive age with TST should incorporate SA as part of their initial treatment protocol.